The Effects of the Use of Colloquial Expressions of Pre-Service Teachers to Students - Ubando, Mary Grace E. (Asian Journal of Multidisciplinary Studies, 2021)
This study bears significant purpose in improving the pre-service teachers' instructional delivery, classroom management, comprehension and vocabulary building of their students by objectifying to determine the status of colloquial expressions in their teaching. It considers the profile of the respondents (pre-service teachers) and their knowledge about the prominent colloquial expressions in their community. Additionally, the study gave them possible situations in the classroom related in their instructions, classroom management and comprehension development and vocabulary building for their students, where the colloquial expressions can be applied. The study has made use of descriptive design and to accompany the researchers to gather significant data, questionnaire that is presented through Likert scale method was also utilized. The results have found that majority of the respondents are female pre-service teachers, and they have large acceptance of using colloquial expressions in their daily communications. However, majority of the pre-service teachers do not prefer to utilize colloquial expressions when their instructional delivery is concerned, and the data only showed partial progress in the level of use of colloquial expressions when pre-service teachers manage the classroom. Similarly, when it comes to the comprehension of the students, colloquial expressions are frequently used by pre-service teachers, but the language has been still considered as not the appropriate means to be used which is same as through when targeting vocabulary building among students. To conclude, colloquial expressions has only become a part of the communication outside the academic world where only the standard language is preferred to be dominant over other words and expressions that were influenced by technology and present generations of speakers despite the instances in the classroom and teaching that shows probability of using colloquial expressions for intellectual improvement. Thus, it is recommended that educators should allow students to discover how creative they are as parts of 21st century speakers by knowing how flexible the language can be. Furthermore, formal approach to learning should be prioritized by both students and pre-service teachers by carefully examining the language that they are using and its impact to their improvement.